Does Macroeconomics and Human Development Index Affect Zakat Performance? - Faris Shalahuddin Zakiy; Anik Gita Yuana; Alifya Nurul Falach; Fitria (Journal of Islamic Economics and Finance Studies, 2024)
Macro variables and the Human Development Index are among the influential factors affecting the amount ZIS collection in Indonesia. The impact has been that the realization and potential of ZIS collection are not balanced when compared to the number of Muslim populations in Indonesia. This research aims to examine the impact of macroeconomics and human development index on zakat performance in Indonesia. Zakat performance is measured using the natural log of the total receipt of ZIS obtained from 39 zakat management organizations from 2011 to 2022, totaling 206 observations. The independent variables in this study are proxied by macroeconomics (i.e., inflation and number of employed people) and human development index. The data were analyzed using a panel data estimation technique as known pooled least square. The empirical results of this study found that inflation has a negative and insignificant effect on zakat performance. Number of employed people do not affect zakat performance. Meanwhile, human development index has a positive and significant effect on zakat performance. Synergy and coordination among zakat management organizations and the socialization of zakat literacy become essential factors in realizing the potential of zakat that has not been optimally collected. Additionally, the government can create a policy-making zakat mandatory for muslim communities by implementing good governance.